Do protectionist trade policies integrate domestic markets? Evidence from the Canada-U.S. softwood lumber dispute - Jinggang Guo; Craig Johnston (Bank of Canada, 2020)
We consider the effects of protectionist trade policies on international and domestic market integration, using evidence from the long-standing softwood lumber trade dispute between Canada and the United States. The benefits of trade liberalization are widely acknowledged, including better home-to-foreign price transmission due to reduced tariffs and lower trade costs between countries. Yet in recent years we see efforts to protect specific domestic groups, including producers, through a revival of protectionist trade policies. Such policies could improve the home-to-home price transmission across domestic markets as consumers may seek lower-cost alternatives domestically. We investigate these ideas using a bi-variate three-regime threshold vector error-correction model (TVECM) to examine the spatial price transmission between Canadian and U.S. markets and within U.S. domestic markets. We do that by introducing a structural break at the start of an effective free trade period within our sample. The results suggest that duty-free treatment for imported Canadian softwood lumber substantially lowers the transaction costs between the two nations. Prices are more easily transmitted from the Canadian market to the U.S. at a higher speed, but the speed of price transmission in the reverse direction is not statistically significant. The U.S. domestic market experienced a higher speed of price adjustment across domestic regions prior to the free trade period, which provides evidence that protectionist policies lead to better domestic market integration.
Keywords: F1; F13; Q17; 330; International topics; Market structure and pricing; Trade integration